2020
DOI: 10.3389/fcvm.2020.577248
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention Implantable Cardiac Defibrillators: A Townsville District Perspective

Abstract: Background: Despite major advances in treating patients with severe heart failure, deciding who should receive an implantable cardiac defibrillator (ICD) remains challenging. Objective: To study the risk factors and mortality in patients after receiving an ICD (January 2008-December 2015) in a regional hospital in Australia. Methods: Eighty-two primary prevention patients received an ICD for ischemic cardiomyopathy (ICM, n = 41) and non-ischemic cardiomyopathy (NICM, n = 40) with 4.8-yrs follow-up. One patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Our analysis also found that the fQRS patients were significantly 1.5 years older than non-fQRS patients and had a 12% increased incidence of diabetes. Multiple studies have shown that age is not a contributing factor to VA in ICD patients (Santangelo et al, 2021), (Bergau et al, 2017), and we and others have found that comorbidities are not often associated with VA or appropriate ICD therapy (Engstrom et al, 2020). While some studies have demonstrated a link between diabetes and VA (Grisanti, 2018), others have reported the opposite (Juhani Junttila et al, 2020), which may be related to HF…”
Section: Fqrs Is Associated With Ventricular Arrhythmias In Hf Patientsmentioning
confidence: 76%
See 3 more Smart Citations
“…Our analysis also found that the fQRS patients were significantly 1.5 years older than non-fQRS patients and had a 12% increased incidence of diabetes. Multiple studies have shown that age is not a contributing factor to VA in ICD patients (Santangelo et al, 2021), (Bergau et al, 2017), and we and others have found that comorbidities are not often associated with VA or appropriate ICD therapy (Engstrom et al, 2020). While some studies have demonstrated a link between diabetes and VA (Grisanti, 2018), others have reported the opposite (Juhani Junttila et al, 2020), which may be related to HF…”
Section: Fqrs Is Associated With Ventricular Arrhythmias In Hf Patientsmentioning
confidence: 76%
“…Mortality is most likely a 'systems failure' comprising a weak heart and many underlying comorbid conditions and mechanisms, some of which we have discussed above, and many that are currently unknown (Engstrom et al, 2020). For example, some comorbidities such as obstructive sleep apnea predispose patients inappropriate ICD therapy, which may increase mortality risk (Engstrom et al, 2020).…”
Section: Fqrs Is Associated With All-cause Mortality In Heart Failure Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…OSA has been implicated as a contributor to secondary rhythm-related complications of other cardiovascular diagnoses, including myocardial infarction and heart failure [71,72]. Among patients with permanent pacemakers that are largely implanted for sinus or AV nodal diseases, the prevalence of previously unrecognized OSA is quite high, raising the question of whether appropriate OSA treatment might have resulted in fewer device implants [73]. In patients with non-ischemic cardiomyopathies who have implanted cardiac defibrillators for the primary prevention of sudden death, OSA has been associated with an increased rate of inappropriate shocks [74].…”
Section: Why Will This Patient Not Get Better? the Impact Of Obstructive Sleep Apnea On Treatment And Outcomes In Cardiac Rhythm Disordermentioning
confidence: 99%